(untitled) (PAAN Journal, 2026)
Sri Lanka is experiencing extreme weather events, including intense rainfall, prolonged droughts, and rising temperatures, driven by recent climate change. Despite policies to mitigate climate change, the effectiveness of government intervention in Sri Lanka is problematic. The main objectives of this study are to examine the reasons for the less effectiveness of government interventions and to explore the community’s preparedness for climate change. Based on qualitative research methods, this study utilizes both primary and secondary data. Six villages considered highly disaster-prone were selected purposefully, in the Passara Divisional Secretariat in the Badulla District. Data was collected with the assistance of undergraduates of the Public Administration Department of the University of Sri Jayewardenepura using semi structured open-ended questions. Narrative analyses were employed to present the data. The effectiveness of the government intervention was not satisfactory due to low awareness of early warning systems and evacuation plans, the lack of secure shelters, inadequate post disaster support, a mismatch in relocation land, inequitable subsidy distribution, inadequate long-term recovery support and limited community participation. Several policy measures are suggested to improve the effectiveness of government intervention. The study provides valuable insights for improving disaster preparedness and response strategies by identifying gaps in government intervention and community preparedness for disaster mitigation in the country.